2007
DOI: 10.1111/j.1468-1331.2007.01797.x
|View full text |Cite
|
Sign up to set email alerts
|

Action and object naming in Parkinson's disease without dementia

Abstract: The present study aimed to assess the ability in objects and actions naming in Parkinson's disease (PD) patients. Further, we wished to assess the effect of a particular conceptual dimension, i.e. manipulability, on the naming of object and actions. Patients were recruited from the Department of Neurology, University of Brescia. Thirty-two were diagnosed as PD, according to published criteria, and 15 healthy volunteers matched in age and education to patients' sample. All patients underwent a detailed clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 33 publications
(36 reference statements)
5
84
1
Order By: Relevance
“…naming [27,28], verbal fluency [29], related-word production [30]). Other reports have found that PD patients exhibiting difficulties in both actionverb and noun processing were more impaired in the former during word naming [31] and word generation [32], and that they improved action naming more than object naming upon stimulation of the subthalamic nucleus [33].…”
Section: Action-language Impairments In Parkinson's Diseasementioning
confidence: 91%
“…naming [27,28], verbal fluency [29], related-word production [30]). Other reports have found that PD patients exhibiting difficulties in both actionverb and noun processing were more impaired in the former during word naming [31] and word generation [32], and that they improved action naming more than object naming upon stimulation of the subthalamic nucleus [33].…”
Section: Action-language Impairments In Parkinson's Diseasementioning
confidence: 91%
“…Note, at this juncture, that virtually all studies on language processing in PD have been conducted with non-demented patients (Bertella et al, 2002;Boulenger et al, 2008;Cotelli et al, 2007;Grossman, Carvell, Stern, Gollomp, & Hurtig, 1992;Grossman et al, 2003;Herrera & Cuetos, 2012;Lieberman, Friedman, & Feldman, 1990;Lieberman et al, 1992). However, recent clinical research demonstrates that PD patients can manifest cognitive impairment even without reaching levels of dementia.…”
Section: Introductionmentioning
confidence: 91%
“…We assessed linguistic (syntactic processing, action-verb production) and semantic (actionaction and object-object association) skills using tasks which have proven sensitive to subtle impairments in neurodegenerative motor disorders, including PD (Cardona et al, 2013;Colman, Koerts, Stowe, Leenders, & Bastiaanse, 2011;Cotelli et al, 2007;Ibáñez et al, 2013;Lieberman et al, 1990), Huntington's disease (Kargieman et al, 2014;Saldert, Fors, Stroberg, & Hartelius, 2010), and motor neuron disease (Bak & Hodges, 2004;Cobble, 1998). All tasks were administered in Spanish, the participants' mother tongue.…”
Section: Language Skillsmentioning
confidence: 99%
“…PD patients thus have difficulties retrieving the phonological form that is the label of an exemplar (Levelt et al, 1991). In addition, in PD, action naming is often found to be more impaired than object naming (Bertella et al, 2002;Cotelli et al, 2007), a phenomenon also observed in agrammatic/Broca's aphasic patients. Related to this, Signorini and Volpato (2006) found that PD patients were impaired on an action fluency task but not on semantic and phonemic fluency tasks.…”
Section: Single Word Production Tasksmentioning
confidence: 99%